The cool sound of tubes [vacuum tube musical applications]. - Barbour, E.
Although solid-state technology overwhelmingly dominates today's world of electronics, vacuum tubes are holding out in small but vibrant areas. Here, the author describes how music applications are one of the last remaining domains dominated by vacuum tubes, and how the devices flourish and even innovate in this field
Keywords: Definitions; Guitar amplifiers; Music applications; Professional audio gear; Vacuum tubes